2016
DOI: 10.1053/j.gastro.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Analyses of Inflammatory Bowel Disease−Associated Colorectal Cancers

Abstract: BACKGROUND & AIMS A long duration of inflammatory bowel disease (IBD) increases the risk for colorectal cancer (CRC). Mutation analysis of limited numbers of genes has indicated that colorectal tumors that develop in patients with IBD differ from those of patients without IBD. We performed whole-exome sequencing analyses to characterize the genetic landscape of these tumors. METHODS We collected colorectal tumor and non-neoplastic tissues from 31 patients with IBD and CRC (15 with ulcerative colitis, 14 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
204
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(226 citation statements)
references
References 92 publications
21
204
1
Order By: Relevance
“…In this study, we found a much lower mutational rate of KRAS than that of sporadic cancer, compatible to a previous report (19). KRAS plays a key role in intracellular signal transduction pathways, and its mutation is observed in approximately 40% of CRC.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found a much lower mutational rate of KRAS than that of sporadic cancer, compatible to a previous report (19). KRAS plays a key role in intracellular signal transduction pathways, and its mutation is observed in approximately 40% of CRC.…”
Section: Discussionsupporting
confidence: 92%
“…This difference might be due to the few adenomas exhibiting a high number of mutations, perhaps they are beginning to exhibit a hypermutable phenotype. While testing for MSI was not performed on the adenomas, the adenoma from sample ID 3 which contained 585 non‐synonymous mutations contained both a POLE (L1561fs) and a POLD3 mutation (Q104fs) consistent with a hypermutable phenotype 32. No known cause for hypermutability was identified in the adenoma from sample ID 6 which contained 434 non‐synonymous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This process includes the acquisition of sequential mutations leading to the loss of adenomatous-polyposis coli (APC) tumor suppressor, activation of the oncogene KRAS, and loss of the TP53 tumor suppressor (27). Interestingly, in colon cancers preceded by chronic inflammation due to IBD, the kinetics of the genetic alterations are different, as TP53 is lost early in disease progression and APC mutations are not as frequently observed compared to sporadic colon cancer (28,29). These data suggest that inflammation may induce novel mechanisms to drive cellular proliferation and survival, resulting in tumorigenesis.…”
Section: Inflammation and Cancermentioning
confidence: 99%